The diary of a space traveller and other stories - Ray, Satyajit, 1921-1992.; Majumdar, Gopa. (New Delhi : Puffin Books ; New York, N.Y. : Penguin Books, 2004)
For children.
Stories.
"The exploits of professor Shonku."
Keywords: Ray, Satyajit, -- 1921-1992 -- Translations into English; Children's stories, Bengali -- Translations into English